Pendampingan Kelompok Usaha Nelayan Melalui Penyuluhan Penanganan Hasil Tangkapan di Kecamatan Babelan, Kabupaten Langkat, Sumatera Utara - Sobariah Sobariah; Lenny S Syafei; Ali Akbar (Unri Conference Series: Community Engagement, 2021)
Fisheries business in the field of fishing in Babalan District, Langkat Regency, which is close to the coastline, results in the production of fish caught of various types, namely Bloat, Shrimp and crab, the results obtained by fishermen are very high, but in terms of handling the quality of fish catches, fishermen in Babalan District are still not good in maintaining the quality and freshness of the fish, because there is no use of ice on the caught fish. Soit affects the selling price of fish because the quality of fish is low. The counseling material is handling the catch on the ship using ice. The method used is a demonstration method aimed at improving the quality of fishermen's catches so that they can increase the selling price of fish, and counseling activities at group meetings, where the group is a joint organization. The results of the demonstration on how to handle caught fish, namely fishermen have understood how to handle fish using ice on fish to maintain the quality of fish after being caught and sold. The results of the extension evaluation on the knowledge aspect increased 64%, the skill aspect of 35 skilled fishermen, and 16 fishermen applied the adoption of innovations regarding the handling of caught fish using ice. Business analysis shows a profit of more than IDR 1,748,500 per fishing activity.